Trade Group Anatomy Structure and Usage of Nyatoh Wood in The Genus of Palaquium - Kustin Bintani Meiganati; Widya Gumilar Yuldareza Harta; Ina Lidiawati; Kridianto (Universitas Nusa Bangsa, 2023)
Based on the classification of trade timber species based on the Decree of the Ministry of Forestry No. 163 of 2003, wood species originating from the genera Palaquium, Payena, and Ganua/Madhuca are categorized as Nyatoh wood. The three genera most commonly found in the Indonesian timber trade are wood from the genus Palaquium. The utilization of wood and its economic value can be determined by looking at the characteristics of its anatomical structure. Therefore, it is necessary to observe the anatomical structure of the genus Palaquium wood. Observation of the anatomical structure of wood using the book